Solitary Fibrous Tumor Arising from the Colonic Wall: A Case Report - Jennifer L. Mc Garry; Fintan R. Ryan; Zi Q. Ng (World Journal of Colorectal Surgery)
Solitary fibrous tumors (SFTs) are defined as fibroblast mesenchymal neoplasms. They occur in 0.35 per 100,000 individuals and most commonly occur in the pleura. Surgical resection is the mainstay of treatment. Our case aims to highlight the presentation, imaging findings, and management of colonic SFTs. We describe the case of a 48-year-old woman presenting with back pain and constipation. Computed tomography of the abdomen/pelvis revealed a large mass encompassing the terminal ileum and right hemi colon, suggesting gastrointestinal stromal tumor. Colonoscopy did not reveal any intraluminal lesion. Intraoperative findings revealed a right abdominal mass adherent to the cecum and terminal ileum without liver or peritoneal disease. The patient underwent a standard oncological right hemicolectomy. Histopathology revealed spindle cell neoplasm with foci of prominent vasculature and a positive signal transducer and activator of transcription 6 stain, supporting a diagnosis of SFT. Colonic SFTs are rare and usually benign in nature. To date, guidance with respect to treatment is dependent on case reports and case series.